MODERN SLAVERY IN INDONESIA : STUDY CASE OF MARITIME SLAVERY IN BENJINA KABUPATEN KEPULAUAN ARU MALUKU - Anastazia N Wattimena (Journal of Islamic World and Politics, 2020)
The case of maritime slavery that took place in Benjina, significance unpopular, and isolated area in easternmost part of Indonesia shook the world. Hundreds of foreign shipman, seafarers were found enslaved for years. Forced by the captains of Thailand ships vessels from PT. Pusaka Benjina Resources to work long and extra hours without being given any appropriate payments and food along the way. This paper use secondary data from books, journals, articles, both online and paper based to gather all related information. This paper also uses the theory of modern slavery as management practice to analyze the pushing factors of this slavery cases. Hoping that the same case will no longer happen in the future. Since, slavery in fishing industry have happened in so many sea based countries in the world, include Indonesia.